The problems and motivational drivers in teaching technical terms: a study on educators at an institute of higher learning / Noraziah Mohd Amin...[et al.] - Mohd Amin, Noraziah; Razali, Wan Noorli; Abdul Rahman, Noor Azam; Mohd Amin, Norhasni (2019)
In teaching vocabulary, it is common for instructors to face some difficulty especially in teaching low-frequency words like technical terms. Since teaching technical terms can be challenging for some teachers, it is significant to discover what could motivate or demotivate their teaching of technical words. To address this issue, the present study was conducted with the aims to investigate the problems faced by 29 educators who were appointed as the facilitators of the English Log Book Program at an institute of higher learning in Nibong Tebal, Penang, Malaysia. It was discovered that the majority of the respondents, 51.7% (M= 3.72, SD= 1.066) agreed that teaching technical terms would be easier if there were Malay equivalents of the same terms (item 7). The findings also indicated that most respondents, 21 instructors (72.4%, M= 4.17, SD= 0.602) revealed that it was their responsibility to ensure that their students were able to understand the technical terms taught as they chose the response option, “agree” for item 13. Having the mission to ensure their students’ comprehension of the technical terms and feeling responsible for this task is obviously one of the instructors’ motivational drivers in teaching their students this category of words.